Landscape enclaves: wine capitalism and luxury tourism in Mendoza, Argentina - Pastor, Gabriela Claudia (2020)
Rural territories in the province of Mendoza, Argentina, particularly those located in the Uco Valley, have been affected by severe transformations connected to two key factors: first, the national state's (de)regulation of water use and, second, the dramatic expansion of capital into winemaking and tourism. These activities have been developed on former livestock farming areas, turning them into fresh produce farms where food production is carried out in a "natural landscape" of unquestionable beauty: the iconic scenery of Mendoza. This article deploys the concept of extractivism to analyze "enclaves of commodity landscapes" associated with high-end wine tourism. Its purpose is to show the extent to which high-end wine tourism requires a sleek and highly aestheticized enclave landscape in order to enable the commodification of singular experiences. This article suggests that: 1) The development of tourism enclaves commodifies the landscape so as to provide the sense of a unique touristic experience; 2) the development of these enclaves is underpinned by the extraction of common, collectively-constructed goods.